Clinical Impact of Structured Follow-up After Pancreatic Surgery. Issue 6 (July 2016) - Tjaden, Christine; Michalski, Christoph W.; Strobel, Oliver; Giese, Nathalia; Hennche, Anne-Kathrin; Büchler, Markus W.; Hackert, Thilo
Abstract : Objectives: Structured follow-up after surgery for pancreatic ductal adenocarcinoma (PDAC) remains controversial and is currently not recommended due to a supposed lack of therapeutic consequences. Furthermore, it is not clear whether noncancer patients after pancreas resection need to be seen in the clinic on a regular basis. The present study analyzed how follow-up after pancreatic surgery affected postoperative treatment and long-term outcomes. Methods: Data of all postoperative visits in a specialized outpatient clinic for pancreatic diseases were analyzed for a 1-year period with regard to symptoms, diagnostic procedures, and therapeutic consequences. Results: Six hundred eighteen patients underwent 940 postoperative follow-ups. Nearly half of them needed a change of medication due to altered pancreatic function. In 74 (40%) of 184 resected PDAC patients, recurrence (local or systemic) was detected during follow-up, although only 19 of these had shown associated symptoms (26%). In all patients with recurrence, a cancer-directed treatment was induced. Eleven (69%) of 16 patients with isolated local recurrence were referred for reresection. Conclusions: Follow-up examinations are a substantial part of the clinical management after pancreas resections. Follow-up is particularly important for PDAC because recurrence is often asymptomatic, but its detection allows for therapeutic interventions and potentially improved prognosis. This should be implemented in future guidelines.